Record of the goblin shark Mitsukurina owstoni (Chondrichthyes: Lamniformes: Mitsukurinidae) from the south-western Atlantic - Rincon, Getulio; Vaske, Teodoro [UNESP]; Gadig, Otto B.F. [UNESP] (Cambridge University Press (CUP), 2014)
This paper reports the first well-documented specimen of the goblin shark, Mitsukurina owstoni in the south-western Atlantic, based on a mature male measuring 3152 mm total length, caught on 27 November 2008 off the Rio de Janeiro coast, south-east Brazil.
Keywords: goblin shark; Mitsukurina owstoni; occurrence; south-western Atlantic